A Study on the Development of the Make-shift Heat Pump for Refugee Camp: A Case Study of Borneo State, Nigeria - Muhammad Izzat Nor, Ma'arof; Vinod Krishnan, K.Arvindra Dass; Hazran, Husain; Choo, Wou Onn; Girma, Tadesse Chala (INTI International University, 2019)
The poor and low temperatures living conditions in the refugee camps are noted to be one of the contributing factors in the widespread of airborne related diseases. Hence, the introduction of heat pump in the camps could minimize the hazard. However, in-situ repair for copper refrigerant pipeline would be challenging due to limited resources. The objective of this paper was to study on the plausibility of utilizing aluminium tin-cans as temporary in-situ repair for copper refrigerant pipeline at the Nigerian refugee camps. In achieving this, a mathematical model of the pipeline was formulated – consisting of the thermodynamic aspects, pressure drop and maximum internal design pressure of the pipeline. The mathematical model was validated using HVAC simulation and computational fluid dynamics simulations being CoolPack and ANSYS. The mathematical model was able to prove that while the thickness of the pipe does not have a significant impact on the heat loss of the system but has a significant impact on the internal design pressure of the pipeline. The simulations were able to validate the mathematical model with the percentage errors of less than 5%. As such, the mathematical model was able to determine the optimum thickness of the pipeline being 0.12mm. From this, it is concluded that the material and the design of the pipeline is suitable for usage for in-situ repairs and maintenance at the refugee camps.